2021
DOI: 10.1093/nar/gkab075
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for RNA recognition by the N-terminal tandem RRM domains of human RBM45

Abstract: RBM45 is an RNA-binding protein involved in neural development, whose aggregation is associated with neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) and frontotemporal lobar dementia (FTLD). However, the mechanisms of RNA-binding and aggregation of RBM45 remain unelucidated. Here, we report the crystal structure of the N-terminal tandem RRM domains of human RBM45 in complex with single-stranded DNA (ssDNA). Our structural and biochemical results revealed that both the RRM1 and RRM2 of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…This suggests that the C-terminal RBDs of RBM45, comprised of the HOA and RRM3 domains, work cooperatively to recognize m 6 A. This is consistent with a recent study showing that the N-terminal region of RBM45 does not preferentially bind m 6 A ( Chen et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This suggests that the C-terminal RBDs of RBM45, comprised of the HOA and RRM3 domains, work cooperatively to recognize m 6 A. This is consistent with a recent study showing that the N-terminal region of RBM45 does not preferentially bind m 6 A ( Chen et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…A previous study found that the HNRNPA2B1 protein binds m 6 A, presumably through its RRM domains ( Alarcón et al, 2015 ), but subsequent work suggests that the RRMs in this protein do not bind m 6 A directly ( Wu et al, 2017 ). A recent structural study showed that the N-terminal RRM1 and RRM2 domains of RBM45 do not bind m 6 A ( Chen et al, 2021 ), which is consistent with our data. However, potential roles of the HOA domain or RRM3 in m 6 A recognition were not examined.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, hrp1 C1-RRM contains an extra F202 (Figure 2). Because of difficulties in the formation of ordered ssRNA complexes with these RRM motifs, sometimes ssDNA was used in study instead, 39 which provides only limited information about RNA-RRM interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of different binding configurations of nucleotide in FIR RRM1 prompted us to investigate whether the observed 5 0 -end nucleotide binding configuration resembled interactions observed in other RRM-ssDNA/RNA complexes. We randomly chose five structures of other nucleic acid-bound RRM1 motifs, including human RBM45 [22] (PDB ID: 7CSZ), DAZL (azoospermia (DAZ)-like) [23] (PDB ID: 2XS5), hnRNP A1 [8] (PDB ID: 5MPG), U2AF2 [24] (PDB ID: 6XLW), and IMP3 [25] (PDB ID: 6GX6), for royalsocietypublishing.org/journal/rsob Open Biol. 13: 230031…”
Section: Diverse Nucleic Acid Binding Configurations In Different Rrm...mentioning
confidence: 99%